Highly Accreting Quasars at High Redshift - Martínez-Aldama, Mary L.; Del Olmo, Ascensión; Marziani, Paola; Sulentic, Jack W.; Negrete, C. Alenka; Dultzin, Deborah; Perea, Jaime; D'Onofrio, Mauro (Frontiers in Astronomy and Space Sciences, 2018)
We present preliminary results of a spectroscopic analysis for a sample of type 1 highly accreting quasars (LLedd>0.2) at high redshift, z~2-3. The quasars were observed with the OSIRIS spectrograph on the GTC 10.4 m telescope located at the Observatorio del Roque de los Muchachos in La Palma. The highly accreting quasars were identified using the 4D Eigenvector 1 formalism, which is able to organize type 1 quasars over a broad range of redshift and luminosity. The kinematic and physical properties of the broad line region have been derived by fitting the profiles of strong UV emission lines such as AlIII, SiIII and CIII. The majority of our sources show strong blueshifts in the high-ionization lines and high Eddington ratios which are related with the productions of outflows. The importance of highly accreting quasars goes beyond a detailed understanding of their physics: their extreme Eddington ratio makes them candidates standard candles for cosmological studies.